Evaluation of a starch-based double layer scaffold for bone regeneration in a rat model - Requicha, J. F. (2014)
Damages in the maxillofacial bones are frequent in humans following trauma, metabolic diseases, neoplasia, or inflammatory processes. Many of the available treatments to regenerate bone are often ineffective. The goal of this work was to assess the in vivo behavior of an innovative double-layered scaffold based on a blend of starch and polycaprolactone (SPCL) that comprises a membrane obtained by solvent casting, which aims to act as a guided tissue regeneration membrane, and a wet-spun fiber mesh (in some cases functionalized with osteoconductive silanol groups) targeting bone regeneration. The behavior of the double layer scaffold, functionalized with silanol groups (SPCL-Si) or without (SPCL), was assessed in a mandibular rodent model and compared to a commercial collagen membrane (positive control) and to empty defects (negative control). After 8 weeks of implantation, the micro-computed tomography and the histomorphometric analysis revealed that the SPCL-Si scaffolds induced significantly higher new bone formation compared to the collagen membrane and to the empty defects, although they had a similar performance when compared to the SPCL scaffolds.